Soft Poly(N-vinylcaprolactam) Based Aqueous Particles - Joonas Siirilä; Heikki Tenhu (Acta Chimica Slovenica, 2022)
Soft nanoparticles are an important class of material with potential to be used as carriers of active compounds. Swollen, penetrable particles can act as a host for the active ingredients and provide stability, stimuli-responsiveness and recyclability for the guest. Thermoresponsive colloidal gel particles are especially attractive for such applications due to the extremely soft structure, size and responsiveness. Poly(N-vinylcaprolactam) (PNVCL) is a much studied, popular thermoresponsive polymer. The polymer has low toxicity and the phase transition temperature is close to body temperature. During the phase transition, the polymer becomes less soluble, the particle expels a large part of water and the particle collapses to a more compact form. The diffusion of material in and from the particles is largely affected by this transition.  As the solubility of the polymer changes, so do the interactions with the loaded compound.  This feature article focuses on the synthetic methods, properties and applications of soft PNVCL particles.